A Novel High-Efficiency S-Band Conical Axial Vircator - P. Livreri (IEEE Access)
A VIRtual CAThode oscillatOR (Vircator) is a High-Power Microwave (HPM) vacuum electron device (VED) with applications in the field of health, energy, space, environment, and defense. In this work, a novel approach to increase S-band Vircator efficiency by a conical waveguide for counter Ummanned Aerial Vehicle (UAV) is presented. At first, starting from the geometrical and physical parameter values chosen, an axial vircator is designed. Then, to enhance its efficiency, a conical structure is added into the cylindric waveguide, altering the electron beam dynamic and optimizing the interaction with the virtual cathode. The Particle-in-Cell simulation carried out by CST Studio suite 2024, shows an average output power of 50 MW and an efficiency up to 60% than the basic vircator configuration ones, with an applied voltage of 520 kV and a cathode current of 20 kA at 2.55 GHz.